2003
DOI: 10.1210/me.2002-0356
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transducer and Activator of Transcription 5 Activation Is Sufficient to Drive Transcriptional Induction of Cyclin D2 Gene and Proliferation of Rat Pancreatic β-Cells

Abstract: Signal transducer and activator of transcription 5 (STAT5) activation plays a central role in GH- and prolactin-mediated signal transduction in the pancreatic beta-cells. In previous experiments we demonstrated that STAT5 activation is necessary for human (h)GH-stimulated proliferation of INS-1 cells and hGH-induced increase of mRNA-levels of the cell cycle regulator cyclin D2. In this study we have further characterized the role of STAT5 in the regulation of cyclin D expression and beta-cell proliferation by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 65 publications
4
76
1
1
Order By: Relevance
“…Furthermore, we have recently shown that this up-regulation is mediated by a direct action of STAT5 on the cyclin D2 promoter (Friedrichsen et al 2003). In the present study, we have investigated the effect of GLP-1 on cyclin D mRNA and protein expression in INS-1E cells, and found that this treatment is associated with a specific elevation of cyclin D1 in a time-dependent manner with maximal induction at 6 and 12 h, respectively.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Furthermore, we have recently shown that this up-regulation is mediated by a direct action of STAT5 on the cyclin D2 promoter (Friedrichsen et al 2003). In the present study, we have investigated the effect of GLP-1 on cyclin D mRNA and protein expression in INS-1E cells, and found that this treatment is associated with a specific elevation of cyclin D1 in a time-dependent manner with maximal induction at 6 and 12 h, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…A firefly luciferase reporter construct containing 2·4 kb of the mouse cyclin D1 promoter (kindly provided by Dr Martin Eilers, University of Marburg, Marburg, Germany) along with the internal control plasmid TKrenilla (Promega) were transiently transfected into islet monolayer or INS-1E cells using LipofectAMINE 2000 (Invitrogen Life Technologies) as previously described (Friedrichsen et al 2003) using 2 µl Lipofect AMINE 2000/well. Islet and INS-1E cells were incubated overnight with DNA-lipofectamine-Optimem mix in RPMI 1640 containing 2% HS and Optimem, respectively.…”
Section: Transient Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 48 h cells were exposed to either 150 pg/ml IL-1β for 1, 2, 4, 6, 8, 16 or 24 h or to varying amounts of IL-1β (18.75 pg/ml-2.4 ng/ml) for 6 h. RNA extraction was performed by the TRIzol method (GibcoBRL, Invitrogen, Carlsbad, CA, USA). For analysis of primary rat islet cells, monolayers were transduced with adenovirus encoding Luciferase or SOCS-3 at a concentration of 5×10 8 plaque forming units/ml [36]. The virus titre used was selected by transduction of islet cells with a green fluorescent protein (GFP)-encoding adenovirus and using a concentration giving >95% GFP-positive cells.…”
Section: Methodsmentioning
confidence: 99%
“…T cells from Stat5a/b-deficient mice fail to express cyclin D2 or cyclin D3 in response to anti-CD3 or IL-2 treatment (28). In the pancreatic ␤-cell line INS-1, a dominant negative form of Stat5 partially inhibited growth hormone-mediated expression of cyclin D2 (29), whereas a constitutively active version of Stat5 induced cyclin D2 expression (30). We have previously characterized a Stat5 binding element in the cyclin D2 promoter that is responsive to IL-2R signaling in T cells (31).…”
mentioning
confidence: 99%